Use of an estradiol-based combined oral contraceptives has no influence on attentional bias or depressive symptoms in healthy women. (March 2020) - Scheuringer, Andrea; Lundin, Cecilia; Derntl, Birgit; Pletzer, Belinda; Sundström Poromaa, Inger
Highlights: In this randomized trial, combined oral contraceptive use did not predict depression scores at the end of the trial. Combined oral contraceptive use is not associated with impaired cognitive-emotional processing. The main predictors of self-rated depression during contraceptive use were baseline. trait anxiety and previous mental symptoms during hormonal contraceptive use. Abstract: Combined oral contraceptive (COC) use is associated with small, albeit significant, increases in mental symptom scores, predominantly irritability, depressed mood, and anxiety. Yet, randomized prospective trials are needed to better characterize the women at risk for COC-induced negative mood change. Thus, the primary aim of this sub-study to a placebo-controlled randomized trial was to determine whether COC use influences emotional interference by negative and positive stimuli. Secondly, we wanted to evaluate what factors would predict depressive symptoms at the end of the trial, taking personality factors, history of mental disorders and other demographic factors into account. Sixty-nine women were included, randomized to three cycles of treatment with a COC (1.5 mg estradiol and 2.5 mg nomegestrolacetate) or placebo. An emotional verbal Stroop task was used to measure interference of emotional stimuli, in which participants were asked to only name the color of a presented word, while ignoring the meaning of the word. Four different word categories were used; neutral, positive, depression, and anxiety. For the second aim of the study, rating on the Montgomery-Åsberg Depression Rating Scale during the final days of the trial was used as outcome. We found no interaction between emotional verbal Stroop word category and treatment, indicating that COC treatment did not evoke any differences in emotional interference to the three word categories. Significant predictors for depressive symptoms at the end of the trial were trait anxiety at baseline and prior adverse mood effects by hormonal contraceptive use. Treatment (i.e. whether women had been treated with the COC or placebo) did not play a role in predicting depression scores at the end of the trial. In conclusion, we found no evidence that combined oral contraceptive use is associated with impaired cognitive-emotional processing. Instead, the main predictors of self-rated depression at the end of the trial were baseline trait anxiety and previous mental symptoms during hormonal contraceptive use.